2013
DOI: 10.1155/2013/385604
|View full text |Cite
|
Sign up to set email alerts
|

CD133 Expression in Normal Skin and in Epithelial Cutaneous Tumors

Abstract: Background. Expression of human CD133 (human prominin-1) in cancer cells has been postulated to be a marker of stemness and is considered as a putative marker of cancer stem cells (CSCs). We designed a study to describe the expression pattern of CD133 in normal skin and in epithelial cutaneous neoplasms. Methods. The CD133 immunohistochemical expression of forty-three eccrine and apocrine tumors was compared to that observed in other epithelial tumors of the skin. In addition, flow cytometry was used to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The main markers used for isolation and identification of CSCs include surface cell-adhesion molecules (e.g., CD44, CD133, and EpCAM) and cytoprotective enzymes (such as aldehyde dehydrogenase, ALDH). However, the surface markers that are used to isolate or identify CSCs from diverse malignant tissues are expressed not only by CSCs, but also by many normal tissues [ 20 , 21 , 22 , 23 , 24 ]. Fox et al revealed that normal human tissues express different CD44 isoforms; for instance, normal epithelial tissues and some tumors express a wide range of variants at high levels.…”
Section: Unique Features Of Cscsmentioning
confidence: 99%
“…The main markers used for isolation and identification of CSCs include surface cell-adhesion molecules (e.g., CD44, CD133, and EpCAM) and cytoprotective enzymes (such as aldehyde dehydrogenase, ALDH). However, the surface markers that are used to isolate or identify CSCs from diverse malignant tissues are expressed not only by CSCs, but also by many normal tissues [ 20 , 21 , 22 , 23 , 24 ]. Fox et al revealed that normal human tissues express different CD44 isoforms; for instance, normal epithelial tissues and some tumors express a wide range of variants at high levels.…”
Section: Unique Features Of Cscsmentioning
confidence: 99%
“…Therefore, it is very important to identify any kind of biomarker related to CSC, which may provide vital information such as risk of metastasis, resistance to therapy, and recurrence. There are studies [ 96 , 129 ] that investigated the role of CD133 (CSC biomarker), a transmembrane glycoprotein present in normal hematopoietic stem cells responsible for proliferation and differentiation in various types of cancers, including skin cancer, demonstrating that overexpression of this protein is correlated with poor prognosis [ 46 , 76 81 ]. Samples of cSCC tissue were analyzed and it was observed that increased expression of CD133 was correlated with low differentiation and advanced tumor stage.…”
Section: Proteic and Other Potential Biomarkers Of Squamous Cell Cmentioning
confidence: 99%
“…The function of Prom1 is unknown, but its specific localization suggests that PROM1 is involved in the organization of plasma membrane protrusions, and suggests that PROM1 might be important in maintaining an appropriate lipid composition within the plasma membrane ( 12 ). In addition, PROM1 has been identified in the apical plasma membrane of epithelial cells of pancreas ( 13 ), liver (canals of Hering, interlobular ducts) ( 14 ), kidney ( 15 ), prostate ( 16 ), and skin ( 17 ). In the small intestine in mouse, Prom1 marks rare stem cells, as well as transit-amplifying progenitor cells ( 6 ).…”
Section: Introductionmentioning
confidence: 99%